ANALISIS CURRENT RATIO DAN EARNING PER SHARE TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Lamtiur Pasaribu, Endang Widiastuti; Banjarnahor, Haposan (LPPM Universitas Putera Batam, 2022)
The food and beverage industry has a very large and rapidly growing group of companies in Indonesia. This industry is also one of the high-growth industries. The development of this branch is inseparable from the population of Indonesia which continues to grow every year. As the population grows, so does the demand for consumer products for puns. The purpose of this study was to determine the effect of the current ratio and profit per share on the company's stock price in the food and beverage industry. This type of research aims to analyze the causal relationship, namely the relationship between one variable and another. The population of this survey is all the financial statements of manufacturing companies listed on the Indonesia Stock Exchange. The annual financial statements of producers listed on the Indonesia Stock Exchange from 2016 to 2020 are used as samples. Information analysis method was carried out according to the Monte Carlo method. As a result, the current ratio does not affect stock prices, but earnings per share have a large effect on stock prices.